CUSTOMER BEHAVIOR TRANSFORMATION: HISTORY AND TODAY - N. V. Barinova (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The current stage of economics development is characterized by high interest in studying economic theory. A key aspect of this theory is studying customer behavior. When Russian economy overcame the economic crisis, the study of issues of the consumption theory acquired an additional importance, as they provide an indicator of economy development showing the degree of meeting the population needs. The author summarized the theoretical material dealing with this line, revised it creatively and gave a forecast of consumption development for the future. Such notions as ‘needs’, ‘consumption’ and ‘customer behavior’ were defined. The algorithm of the process of decision-making about the purchase was provided and factors influencing this process were enumerated. The author shows new trends of shaping a customer choice in conditions of passing-over to digital economy. The article points out that as informational-communications technologies develop, information begins to play a more and more important role in the process of customer decision-making. Apart from that issues of market segmentation were considered, classification of key groups of today’s customers was put forward and groups of customers using ICT in the process of decision-making were identified.